2018
DOI: 10.1093/femsec/fiy169
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature increase on microbial carbon fluxes in the Adriatic Sea: an experimental approach

Abstract: An assessment of the temperature increase effect on processes within the microbial food web provides a better insight into the carbon transfer and energy flow processes in marine environments in the global warming perspective. Modified laboratory dilution experiments that allow simultaneous estimates of protozoan grazing and viral lysis on picoplankton groups (bacteria, Prochlorococcus, Synechococcus and pico-eukaryotic algae) under in situ and 3°C above in situ temperatures were performed at seasonal scale. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 87 publications
5
11
0
Order By: Relevance
“…While the autotrophic picoplankton flux towards predators (both HNF and CIL) increased under all experimental conditions and in all months, the bacterial biomass flux towards HNF in July (maximal HNF grazing on bacteria) and towards CIL in January increased considerably, mainly because of temperature increase. These results confirmed earlier studies in the Adriatic Sea that reported maximal contribution of ciliates to total grazing on bacteria during the winter, while during the warmer period HNF were almost completely responsible for bacterial grazing (Šoli c and Krstulovi c, 1994;Šoli c et al, 2018a). Our study showed that the efficiency of direct carbon transfer from bacteria to ciliates was inversely proportional to the amount of carbon transferred.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…While the autotrophic picoplankton flux towards predators (both HNF and CIL) increased under all experimental conditions and in all months, the bacterial biomass flux towards HNF in July (maximal HNF grazing on bacteria) and towards CIL in January increased considerably, mainly because of temperature increase. These results confirmed earlier studies in the Adriatic Sea that reported maximal contribution of ciliates to total grazing on bacteria during the winter, while during the warmer period HNF were almost completely responsible for bacterial grazing (Šoli c and Krstulovi c, 1994;Šoli c et al, 2018a). Our study showed that the efficiency of direct carbon transfer from bacteria to ciliates was inversely proportional to the amount of carbon transferred.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study carried out in the Adriatic Sea also showed a positive response of autotrophic picoplankton abundance to temperature (Šolić et al, , ). This is in accordance with the idea that planktonic autotrophs and heterotrophs are characterized by different activation energies (Chen and Laws, ).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations